Efektivitas Penggunaan Model Pembelajaran Picture And Picture Terhadap Kemampuan Berpikir Kreatif Siswa - firdaus, zuhairina; Banowati, Eka Nanda; Maula, Alvita Rizki; Ermawati, Diana (Peneliti.net, 2023)
The ability to think creatively is very important for students to develop creativity in solving students' mathematical problems. The low ability of students' creative thinking is a problem in developing students' mathematical problem solving creativity. The purpose of this study was to identify whether there were differences in students' creative thinking skills before and after using the picture and picture learning model. This research was conducted on fifth grade students of SD Negeri 3 Bacin, totaling 24 students. The research method used was quasi-experimental using a one group pretest posttest design. The data collection technique used in this study was a observation and also multiple choice test to measure students' creative thinking abilities. Data analysis was performed using a paired sample t-test. The results showed that the average score on the posttest was higher than the average score on the pretest, which was 70.9%. This shows an increase in students' creative thinking skills after using the picture and picture learning model. In addition, the research results also show that the significance value obtained is 0.000, which means it is smaller than 0.05. Therefore, the null hypothesis (Ho) is rejected. This indicates that there is a significant difference between students' creative thinking abilities before and after using the picture and picture learning model.